PERANCANGAN BUSANA EVENING DENGAN APLIKASI MOTIF BATIK CERITA RAKYAT PANTAI WIDURI - Naila Siva Amalia; Dheasari Rachdantia (Akademi Seni dan Desain Indonesia Surakarta, 2024)
Evening clothing is clothing made from good materials with attractive decorations so that it looks beautiful to be worn by someone at an evening party. The author is interested in developing an evening dress that will be combined with the motifs of the folklore folklore of Thistle Beach. The method used is in the form of designing evening dresses with the application of the motif of the folklore of Widuri Beach. The aesthetic element that appears in this design is the batik cloth with the motif of the folklore of Thistle Beach with decorative depictions. This evening's fashion design uses cotton and satin cotton with a written batik technique. The coloring process uses a reactive dye (procion) and naphtol. This design with the theme of folklore produces an evening dress with the application of the folklore batik motif of Widuri Beach. Design is a way that is felt to be quite effective in raising the existence of batik by utilizing a variety of Indonesian cultures to be used as fashion creations that are aesthetic, have distinctive characteristics, and are unique, especially among young people aged 18-21 years Keyword: Batik, Evening clothing, Folkore, Widuri Beach